Adesão à higienização das mãos em um hospital universitário: o efeito Hawthorne - Kozerski, Dalila (2017)
Monitoring adherence to hand hygiene in our hospital using covert direct observation method (covert observer) has shown poor adherence rates. Some studies suggest that the combination of covert and overt (overt observer) observation methods may offer a more effective approach to increasing the hand hygiene adherence rate in hospital practice. To assess whether the Hawthorne effect (ie, tendency of people to behave differently when they know that they are being observed) commonly associated with the overt direct observation method may encourage adherence to hand hygiene practice in a university hospital. The quality of the hand hygiene technique was also investigated. Prospective direct observational study carried out in a 120-bed tertiary care university hospital. In the first period of the study, covert observation (46 hours) was performed during April to July 2015. In the second period, overt observation (83 hours) was performed during February to April 2016. The observation sessions, with duration of 20 to 30 minutes, were performed randomly in the morning, afternoon and evening shifts. In the overt observation, the quality of the hand hygiene technique was also evaluated. A total of 4360 indications for hand hygiene were recorded during the 129 hours of direct observation. The overall adhesion rate in the overt observation (43%, 1299/3013) was significantly higher than that of covert observation (29%, 391/1347) (P<0.001). Most indications for hand hygiene (76.5%, 3336/4360) were observed before and after contact with the patient. The most neglected steps in the technique of hand hygiene were steps 4 (back of the hands) and 6 (fingertips). The majority (89.37%) of hospital personnel did not perform the 7 steps recommended in the hand hygiene technique. The average time spent on hand hygiene with soap or chlorhexidine and alcohol gel, and its standard deviation, were 34±19s and 14±9.10s, respectively. Despite the poor adherence to hand hygiene and failures to perform the technique, the Hawthorne effect showed a marked influence on hand hygiene adherence, increasing the adherence in overt observation by 48.27%. The results suggest that the combination of overt and covert observation methods may be a valid alternative to promote hand hygiene in hospital practice.